HyperJump Wants To Offer A Nausea-free VR Experience - Zipponews (2022)
Moving around in the world of virtual reality is not without consequences for the body. Thanks to HyperJump, no more car sickness.
Keywords: mediaCoverage; proj--hyperjump3D-newscoverage